Верифікація принципу Парето для доходів від наукової діяльності закладів вищої освіти України - Слав’юк, Ростислав Анатолійович; Тоцька, Олеся Леонтіївна; Slav’yuk, Rostyslav; Totska, Olesia Leontiivna (My University, 2021)
У статті проведено ABC-аналіз показників обсягу надходжень до спецфонду закладів вищої освіти України за результатами наукових і науково-технічних робіт за проєктами міжнародного співробітництва, господарськими договорами та надання наукових послуг за 2016–2018 рр. Перевірено та підтверджено гіпотезу про наявність у цих показниках принципу Парето: виявлено, що 19,595 % (≈20 %) вітчизняних ЗВО забезпечило 79,39 % (≈80 %) загального доходу від наукової діяльності. За результатами ABC-аналізу для ЗВО України із кожної групи запропоновано стратегію комерціалізації результатів наукової діяльності.

The purpose of the article is to verify the Pareto principle in terms of revenues to the special fund of higher education institutions of Ukraine based on the results of scientific and scientific-technical work on international cooperation projects, scientific and scientific-technical work under economic agreements and scientific services. With the help of ABC-analysis of indicators of income from scientific activity, domestic higher education institutions are divided into three groups: A – higher education institutions with a large amount of income from scientific activities; B – higher education institutions with an average level of commercialization of scientific activity; C – higher education institutions with little or no income from research. It was obtained that group A included 29 (19,595 %) higher education institutions of Ukraine, which in 2016–2018 provided paid scientific services in the amount of UAH 739,747 million (79,39 % of the total). Group B was formed by 34 (22,973 %) domestic higher education institutions, whose scientific activity in the analyzed period brought income in the amount of UAH 147,954 million (15,88 % of the total). Group C included 85 (57,432 %) Ukrainian higher education institutions, which earned UAH 44,082 million (4,73 % of the total) as a result of their scientific work. It was found that the Pareto principle 20/80 was reflected in the activities of higher education institutions in Ukraine. Strategies for commercialization of research results for domestic higher education institutions from each group are proposed: group A – leader’s strategy; group B – the applicant’s strategy; group C – strategy of the beginner.
Verification of the Pareto principle for income from scientific activity of higher education institutions of Ukraine
Keywords: принцип Парето; ABC-аналіз; доходи; наукова діяльність; заклади вищої освіти; Україна; Pareto principle; ABC-analysis; income; research; higher education institutions; Ukraine; С10; Е64; G32; I29; L84; 330.13Парето:[378.014.54:001.89